Crows: Exploración creativa a través de tres subgéneros del metal (2024)
In the vast world of music, influences can be as diverse as unexpected. For some, a particular artist or genre can become a inexhaustible source of inspiration, shaping not only musical taste, but also its creative approach. Metal and its subgenres have aroused great interest in me to the point of reaching to be the object of study. This sound full of fury and energy, coherent in my socio-cultural context, but disruptive with the trends and popular thinking of the youth of the time, produced in me an instant connection that still lasts. Without However, while exploring much of its broad spectrum, I felt the need to find your own sound, recombining its elements from a perspective alternative and personal.